Roller girl - Jamieson, Victoria (New York : Dial Books for Young Readers, 2015)
A graphic novel adventure about a girl who discovers roller derby right as she and her best friend are growing apart.
School Library Journal starred, December 2014.
Horn Book Starred, March 2015.
Bulletin of the Center for Children's Books starre, April 2015.
Pub Weekly, January 2015.
Kirkus Starred, December 2014.
Booklist, March 2015.
Keywords: Sports stories; Roller derby -- Fiction; Roller skating -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Sports -- Fiction; Cartoons and comics; Sports -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Graphic novels